2007
DOI: 10.1212/01.wnl.0000251268.41188.04
|View full text |Cite|
|
Sign up to set email alerts
|

Recombinant human acid α-glucosidase

Abstract: Abstract-Background:Pompe disease is a progressive metabolic neuromuscular disorder resulting from deficiency of lysosomal acid ␣-glucosidase (GAA). Infantile-onset Pompe disease is characterized by cardiomyopathy, respiratory and skeletal muscle weakness, and early death. The safety and efficacy of recombinant human (rh) GAA were evaluated in 18 patients with rapidly progressing infantile-onset Pompe disease. Methods: Patients were diagnosed at 6 months of age and younger and exhibited severe GAA deficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
457
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(493 citation statements)
references
References 28 publications
(55 reference statements)
9
457
2
3
Order By: Relevance
“…Outcome assessment in comparison to an appropriately matched natural history or historical control population has been used to support regulatory approval of several therapies targeted to ultra‐orphan populations over the past decade including Myozyme for Pompe disease46 and CEPROTIN for patients with severe congenital protein C deficiency 47. These present results indicate such an approach may also be appropriate for DMD, especially as it would spare declining patients from receiving placebo rather than potentially disease‐altering treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome assessment in comparison to an appropriately matched natural history or historical control population has been used to support regulatory approval of several therapies targeted to ultra‐orphan populations over the past decade including Myozyme for Pompe disease46 and CEPROTIN for patients with severe congenital protein C deficiency 47. These present results indicate such an approach may also be appropriate for DMD, especially as it would spare declining patients from receiving placebo rather than potentially disease‐altering treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ERT prolonged overall survival and ventilator-free survival and reversed cardiomegaly in infantile-onset Pompe disease (Kishnani et al 2007). Motor function was maintained when infants with classic infantile-onset Pompe disease were diagnosed through newborn screening and received very early treatment with ERT (Chien et al 2008;Chien et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that even in cross-reactive immunologic material (CRIM)-negative IPD patients with high-sustained antibody titers, only a subset demonstrated neutralizing antibodies in in-vitro assays. 2,3 Even among those who had neutralizing antibodies, some demonstrated antibodies only to the catalytic domain and not to the uptake domain. However, irrespective of the presence/ type of neutralizing activity, they all experienced poor clinical outcomes.…”
Section: Response To De Vries Et Almentioning
confidence: 99%
“…We previously reported on the counteracting effect of high sustained antibodies in this particular patient. 3 Herbert and colleagues may have missed the fact that only a few adult patients develop high sustained antibodies, which is in contrast to the situation in classic infantile patients. A recent study by Masat et al 4 on behalf of the French Pompe Registry Study Group also concluded that antibodies are not a major concern in adults with Pompe disease.…”
Section: Response To De Vries Et Almentioning
confidence: 99%